Cross-regulation of Pseudomonas motility systems: the intimate relationship between flagella, pili and virulence. (December 2015) - Kazmierczak, Barbara I; Schniederberend, Maren; Jain, Ruchi
Highlights: Particle-tracking algorithms show a wide range of P. aeruginosa motility at surfaces. Asymmetry of c-di-GMP levels in cells correlates with varied motility post-division. Retraction of attached Type IV pili is a signal for increased cAMP production. Surface attachment and cell density are independent signals for increased virulence. Innate immunity distinguishes motile and nonmotile flagella and reacts to the former. Abstract : Pseudomonas aeruginosa navigates using two distinct forms of motility, swimming and twitching. A polar flagellum and Type 4 pili power these movements, respectively, allowing P. aeruginosa to attach to and colonize surfaces. Single cell imaging and particle tracking algorithms have revealed a wide range of bacterial surface behaviors which are regulated by second messengers cyclic-di-GMP and cAMP; the production of these signals is, in turn, responsive to the engagement of motility organelles with a surface. Innate immune defense systems, long known to recognize structural components of flagella, appear to respond to motility itself. The association of motility with both upregulation of virulence and induction of host defense mechanisms underlies the complex contributions of flagella and pili to P. aeruginosa pathogenesis.